Historical Contingency Causes Divergence in Adaptive Expression of the lac Operon - Karkare K; Lai H-Y; Azevedo RBR; Cooper TF (Oxford University Press on behalf of The Society for Molecular Biology and Evolution (SMBE), 2021)
Populations of Escherichia coli selected in constant and fluctuating environments containing lactose often adapt by substituting mutations in the lacI repressor that cause constitutive expression of the lac operon. These mutations occur at a high rate and provide a significant benefit. Despite this, eight of 24 populations evolved for 8,000 generations in environments containing lactose contained no detectable repressor mutations. We report here on the basis of this observation. We find that, given relevant mutation rates, repressor mutations are expected to have fixed in all evolved populations if they had maintained the same fitness effect they confer when introduced to the ancestor. In fact, reconstruction experiments demonstrate that repressor mutations have become neutral or deleterious in those populations in which they were not detectable. Populations not fixing repressor mutations nevertheless reached the same fitness as those that did fix them, indicating that they followed an alternative evolutionary path that made redundant the potential benefit of the repressor mutation, but involved unique mutations of equivalent benefit. We identify a mutation occurring in the promoter region of the uspB gene as a candidate for influencing the selective choice between these paths. Our results detail an example of historical contingency leading to divergent evolutionary outcomes.
Keywords: lac operon, experimental evolution; adaptation; epistasis; gene expression; Adaptation, Biological; Biological Evolution; Escherichia coli; Escherichia coli Proteins; Gene Expression; Gene Expression Regulation, Bacterial; Genetic Fitness; Lac Operon; Lac Repressors; Membrane Proteins; Mutation